Modified Hash to Obtain Random Subset-Tree (MHORST) Using Merkle Tree and Mersenne Twister - Ahmad, Faidhil Nugrah Ramadhan; Barmawi, Ari Moesriami (JOIN (Jurnal Online Informatika), 2025)
The development of quantum computing triggers new challenges in data security, particularly in addressing attacks that can solve complex mathematical problems on the fly. Several hash-based data security methods have been proposed to deal with this threat, one of them being Hash to Obtain Random Subset-Tree (HORST). However, HORST has drawbacks, such as low security, because it only uses one hash round. The security of HORST is already improved by Hash to Obtain Random Subset and Integer Composition (HORSIC). However, HORSIC’s execution time is significantly increased. The problem of this research is the low-security HORST and the high execution time of HORSIC. This research proposes a new method, Modified Hash to Obtain Random Subset-Tree (MHORST), which aims to improve the security of HORST and reduce the execution time to less than HORSI’s. MHORST uses Merkle tree, SHA-256 hashes, and Mersenne Twister to build public keys and digital signatures. Based on the experiment results, MHORST reduces the signing time by more than 3.3 times compared to HORST. MHORST reduces the verification time by more than 1.1 times HORST and 17 times HORSIC. Although the security level of MHORST decreases slightly compared to HORSIC, this method is still more secure than HORST against signature forgery.